Erikson’s Fourth Stage of Development: A Deep Dive into Harry Potter’s Character Progression - Theresia Mundi Astuti; Bayu Andika Prasatyo (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2024)
This comprehensive study delves into the character progression of Harry Potter, the protagonist of J.K. Rowling’s renowned series, through the lens of Erikson’s fourth stage of psychosocial development - Industry vs. Inferiority. The primary objectives are to discern the character personality that Harry Potter embodies and to elucidate how this pivotal stage of Erikson’s theory is manifested in the narrative. The writers employed a qualitative research methodology. This study offers a comprehensive portrayal of an event or incident that is directly pertinent to the research focus, providing a precise and unbiased depiction of it. An objective and intrinsic technique is used to assess the primary character. The research underscores the profound impact of external influences on Harry’s journey towards industry, overcoming feelings of inferiority, and ultimately, fostering a robust sense of self. Harry Potter effectively completes the fourth stage, which leads to a healthy personality, by establishing a sense of pride in his work and accomplishment. The findings show that Harry Potter, as the main character, is currently experiencing the fourth phase of Erikson's psychological development. Harry Potter is a heroic protagonist who effectively accomplishes his purpose and demonstrates bravery. Harry Potter is currently in the fourth stage of Erikson's psychosocial development, known as the stage of school-age children. The findings offer valuable insights into the intricate interplay between literature and psychology, shedding light on the nuanced character development in the Harry Potter series.